NordiCon - Språkbanken Text (University of Gothenburg, 2025)
NordiCon is a database that collects medieval North Germanic personal
names in sources outside Scandinavia. It combines formally interpreted
and richly interlinked onomastic data with digitized versions of the
medieval manuscripts from which the data originate and information on the
name tokens’ context.

NordiCon is a database that collects medieval North Germanic personal
names in sources outside Scandinavia. It combines formally interpreted
and richly interlinked onomastic data with digitized versions of the
medieval manuscripts from which the data originate and information on the
name tokens’ context.
NordiCon
Keywords: Language Technology (Computational Linguistics); names; medieval; lexicon; Natural Language Processing; Språkbehandling och datorlingvistik